Performance analysis of Voice Over IP (VOiP) over mobile broadband (HSDPA) / Aspalilla Main - Main, Aspalilla (2010)
This paper focuses on Voice Over IP (VoIP) over mobile broadband. The objective of this paper is to analyze the performance of VoIP over HSP A through two parameters which are the jitter and mouth-to-ear delay parameters. The drive test was conducted to collect real measurement data in live HSDPA network. The data are analyzed to examine the behavior of jitter and mouth-to-ear delay where both of the parameters impact the quality of the conversation made by VoIP. From the experiment result, it is clear that with small packet size and large buffer jitter may bring the large latency and may cause the mouth-to-ear delay. As known, the large number of mouth-to-ear delay dramatically degrades the quality of VoIP call.